SCIENTIFIC AND ORDINARY LANGUAGE IN STRUCTURE OF MODERN SCIENTIFIC DISCOURSE - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article is devoted to the problem of the correlation of scientific and ordinary language in modern scientific discourse.